Efeito da suplementação de cloreto de amônio sobre os equilíbrios eletrolítico e ácido-básico e o pH urinário de ovinos confinados - Ferreira, Danilo O.L. [UNESP]; Santarosa, Bianca P. [UNESP]; Sacco, Soraya R. [UNESP]; Dias, Adriano [UNESP]; Amorim, Rogério M. [UNESP]; Chiacchio, Simone B. [UNESP]; Lisbôa, Júlio A.N.; Gonçalves, Roberto C. [UNESP] (My University, 2014)
The incidence of obstructive urolithiasis in sheep is high, especially in feedlot males, both for meat production, or the breeder of high genetic value. The urinary acidification is one way to prevent this disease and can be performed effectively supplementation with ammonium chloride in the diet, which may facilitate the installation of metabolic acidosis. The blood gas analysis evaluates the acid-base balance of blood in a practical and easy way. In this study, it was evaluated the effect of ammonium chloride on acid-base and electrolyte in feedlot sheep blood gas analysis to determine the occurrence of metabolic acidosis. It was used 100 male lambs, in a feedlot, aged approximately three months. It was constituted three groups: Group I (n=40) that received 400mg/kg/PV of ammonium chloride/animal/day for 21 consecutive days, the time of discontinuation of the urinary acidifiers (M3) and continued clinical follow until the end of the experiment (M6); Group II (n=40), that received 400mg/kg/PV of ammonium chloride/animal/day for 42 consecutive days, Group III (n=20), that did not receive ammonium chloride throughout the experimental period. The moments (M) of samples and clinical assessment were established on seven days of interval, M0 (immediately before the beginning of the treatment with ammonium chloride), M1 (seven days after), M2, M3, M4, M5 and M6, totalizing 56 days of feedlot. The feed consisted of a total mixed ration consisting of 15% of ground hay and 85 % of concentrate, water and mineral salt ad libitum. After 15 days of adaptation to the diet of feedlot, urine samples for measurement of pH, and venous blood for blood gas analysis were collected from all animals at different moments. The urinary acidification was maintained as was the administration of ammonium chloride in GI and GII. The values of Na+ and K+ remained within the normal range for the species. Ammonium chloride caused metabolic acidosis compensated change in GI and GII, confirmed by values of HCO3 - and EB below the reference values, with a normal pH, and high levels of Cl-, and decreased SID. It was concluded that although ammonium chloride to cause decrease of alkalinity in the body, caused no loss in animal development and can be used as a preventive agent obstructive urolithiasis in sheep.
Effect of supplementation of ammonium chloride on electrolyte and acid-base balances and urinary pH of feedlot sheep
Keywords: Acid-base balance; Ammonium chloride; Electrolyte balance; Hyperchloremia; Metabolic acidosis; Small ruminants; Urinary acidifiers; Urolithiasis